Factor sociodemográfico, hábitos alimentarios, actividad física y estado nutricional en gestantes del centro de salud América Y San Antonio, Iquitos 2020 - Bernuy Santana, Francesca Tai (2022)
The objective of this study was to relate and compare the sociodemographic factor, eating habits, and physical activity with the nutritional status of pregnant women from the America and San Antonio health centers. It had a quantitative approach, of a non-experimental type with a correlational and comparative design with a sample of 127 pregnant women; the data was obtained through medical records and surveys of sociodemographic factors, eating habits and physical activity, duly validated. The ages of the pregnant women varied between 20 to 35 years, 86.7% of the CS America and 77.6% of the CS San Antonio are cohabiting, they also reported economic income of weekly salary and secondary education level. Regarding occupation, 70% and 67.2% stated that they were housewives for CS América and CS San Antonio, respectively. According to the pre-pregnancy BMI in CS America, 41% presented normal nutritional status; however, 36.6% were overweight with an excessive weight gain of 45%. 20% had mild anemia, 93.3% claimed to have unhealthy eating habits and 58% performed low physical activity. On the other hand, for CS San Antonio, according to the pre-pregnancy BMI, 38.8% of the pregnant women were normal and overweight, excessive weight gain was 38.8%, 13.4% had mild anemia, 89.6% had unhealthy eating habits and 61.2% perform low physical activity. Therefore, in the CS America there is a significant statistical relationship at the level of study with weight gain, age with hemoglobin; and for CS San Antonio, a statistical relationship was found between pre-pregnancy BMI with age, economic income with hemoglobin, and eating habits with hemoglobin. When comparing there is no difference in the variables studied in both health centers.